Microbial Carriage of Cockroaches at a Tertiary Care Hospital in Ghana. (January 2013) - Tetteh-Quarcoo, Patience B.; Donkor, Eric S.; Attah, Simon K.; Duedu, Kwabena O.; Afutu, Emmanuel; Boamah, Isaac; Olu-Taiwo, Michael; Anim-Baidoo, Isaac; Ayeh-Kumi, Patrick F.
Cockroaches are common in the environment of many hospitals in Ghana; however, little is known about their public health risks. To evaluate potential risks, we investigated the external and internal microbial flora of 61 cockroaches from a tertiary hospital in Ghana and evaluated the antibiotic resistance profiles of the common bacterial species. Standard methods were used in all the microbiological investigations and antibiotic susceptibility testing. A rotavirus carriage rate of 19.7% was observed among the cockroaches. Four types of intestinal parasites were carried externally by the cockroaches, and the most prevalent was Hookworm (4.9%). Eight nosocomial bacteria were isolated from the cockroaches, and the most prevalent was Klebsiella pneumoniae, which occurred internally in 29.5% of the cockroaches and 26.2% externally. Multiple drug resistance among common bacteria isolated from the cockroaches ranged from 13.8% ( Escherichia coli ) to 41.1% ( Klebsiella pneumoniae ). Cockroaches constitute an important reservoir for pathogenic microorganisms, and may be important vectors of multiple resistant nosocomial pathogens in the studied hospital.